A Bayesian network meta-analysis of non-pharmacological interventions for neonatal pain management: a clinical effectiveness comparison - Xu, Lingxue; Xiang, Lali; Pan, Lihui; Xue, Peipei; Li, Juan; He, Yurong; Liu, Hongyan; Hu, Yuwei; Zheng, Bo (Frontiers in Pediatrics, 2025)
BackgroundNewborns are particularly vulnerable to pain, and non-pharmacological methods are frequently employed for pain management due to their lack of side effects. However, there is a lack of comprehensive comparison and ranking of the effectiveness of various non-pharmacological interventions.ObjectiveTo evaluate the effectiveness of non-pharmacological interventions and to determine whether differences exist in the efficacy of various interventions.DesignSystematic review and network meta-analysis.Data sourceRCTs studies in MEDLINE, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials from inception to November 1, 2024.Review methodsUp to November 1, 2024, we conducted a comprehensive search across four databases to identify studies meeting our inclusion criteria. A Bayesian model was employed for the analysis, and heterogeneity was quantified using random-effects standard deviation (RESD), τ², and I² statistics. The certainty of the synthesized evidence was evaluated using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. This study protocol has been registered with PROSPERO.ResultsInitially, we identified 20 citations and included 59 trials involving 2,028 participants for network meta-analysis. Due to many interventions being supported by only one or two original studies, we excluded interventions with fewer than three studies. Ultimately, we identified 13 citations, including 31 trials with a total of 1,141 participants. Regarding efficacy, several interventions were found to be effective. Breast milk (BM), sweet taste (ST), Yakson touch (YT), swaddling, and heel warming (HW) demonstrated significant effectiveness, with mean differences (MDs) in NIPS scores as follows: BM vs. control, −1.71 [95% credible interval (CrI): −2.29, −1.17]; ST vs. control, −1.35 (CrI: −2.13, −0.52); YT vs. control, −1.41 (CrI: −2.09, −0.74); swaddling vs. control, −0.65 (CrI: −1.23, −0.13); and HW vs. control, −0.53 (CrI: −0.89, −0.01). In pairwise comparisons between interventions, significant efficacy differences were observed: BM vs. HW, −1.89 (CrI: −2.70, −1.05); BM vs. non-nutritive sucking (NNS), −1.89 (CrI: −2.70, −1.05); BM vs. ST, −0.88 (CrI: −1.61, −0.11); BM vs. YT, −0.82 (CrI: −1.56, −0.03); BM vs. swaddling, −1.59 (CrI: −2.20, −0.78); NNS vs. ST, 0.98 (CrI: 0.11, 1.89); NNS vs. YT, 1.06 (CrI: 0.12, 2.03); and HW vs. YT, 0.89 (CrI: 0.23, 1.69). Notably, NNS was not found to be effective. The Surface Under the Cumulative Ranking Curve (SUCRA) analysis suggested that BM may be the most effective non-pharmacological intervention for neonatal pain management. SUCRA rankings for the interventions were as follows: BM > ST > YT > swaddling > HW > NNS > control. However, the certainty of the evidence ranged from moderate to very low. Heterogeneity assessments indicated a random-effects standard deviation (RESD) of 0.28 (CrI: 0.04, 0.73) in the consistent model and 0.36 (CrI: 0.01, 1.36) in the inconsistent model, with I² = 100% and τ² = 2.22.ConclusionGiven the limitation of high heterogeneity, this study should be regarded as a clinical effectiveness comparison. Among the included interventions, breast milk (BM), sweet taste (ST), Yakson touch (YT), heel warming (HW), and swaddling were found to be efficacious, while non-nutritive sucking (NNS) was not effective. The top three interventions, based on ranking, were BM, YT, and ST. However, some effects should be interpreted with caution, as they are derived from small sample sizes. Future research should focus on identifying factors associated with individual responses through large, multicenter studies.Implications for Nursing ManagementFindings will inform nurse managers of an ideal environment for the non-pharmacological pain management for newborn.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023399924, PROSPERO CRD42024567338.